A case of cyclic hemoperitoneum in a hemodialysis patient: Encapsulated peritoneal sclerosis complicated by endometriosis and fungal peritonitis. Issue 2 (22nd December 2020) - Yılmaz, Fatih; Bora, Feyza; Çetinkaya, Ramazan; Gelen, Mustafa Tekinalp; Süleymanlar, Gültekin; Ersoy, Fevzi
Abstract: Encapsulated peritoneal sclerosis (EPS) is a rare, but frequently fatal, long‐term complication of peritoneal dialysis. Endometriosis is a common gynecological problem but hemoperitoneum due to endometriosis has been reported to be extremely rare in hemodialysis (HD) patients. A 25‐year‐old female HD patient was admitted to our clinic with nausea, vomiting, abdominal pain, and weight loss for last 3 months. Candida tropicalis and Candida glabrata were isolated in the fungal cultures from peritoneal fluid. Her abdominal computerized tomography scan has shown irregular peritoneal calcifications, diffuse peritoneal thickening, dilatation of the small bowel loops, and cocoon formation which all were typical for EPS. Hemoperitoneum was reported to recur for four times with intervals suggesting menstrual cycles. Her peritoneal biopsy, along with the signs of EPS, has also revealed the presence of endometriosis. The patient died with symptoms of septic shock in the first year of EPS diagnosis.